Additive Prognostic Value of Left Ventricular Systolic Dysfunction in a Population-Based Cohort. (July 2016) - Kuznetsova, Tatiana; Cauwenberghs, Nicholas; Knez, Judita; Yang, Wen-Yi; Herbots, Lieven; D'hooge, Jan; Haddad, Francois; Thijs, Lutgarde; Voigt, Jens-Uwe; Staessen, Jan A.
Abstract : Background—: Techniques of 2-dimensional speckle tracking enable the measurement of myocardial deformation (strain) during systole. Recent clinical studies explored the prognostic role of left ventricular global longitudinal strain (GLS). However, there are few data on the association between cardiovascular outcome and GLS in the community. Therefore, we hypothesized that GLS contains additive prognostic information over and beyond traditional cardiovascular risk factors in a large, population-based cohort. Methods and Results—: We measured GLS by 2-dimensional speckle tracking in the apical 4-chamber view in 791 participants (mean age 50.9 years). We calculated multivariable adjusted hazard ratios for midwall, endocardial, and epicardial GLS, while accounting for family cluster and cardiovascular risk factors. Median follow-up was 7.9 years (5th to 95th percentile, 3.7–9.6). In continuous analysis, with adjustments applied for covariables, midwall, endocardial, and epicardial GLS were significant predictors of fatal and nonfatal cardiovascular (n=96; P <0.0001) and cardiac events (n=68; P ⩽0.001). In the sex-specific low quartile of midwall GLS (<18.8% in women and <17.4% in men), the risk was significantly higher than the average population risk for cardiovascular (128%, P <0.0001) and cardiac (94%, P =0.0007) events. We also noticed that the risk for cardiovascular events increased with increasing number of left ventricular abnormalities, such as low GLS, diastolic dysfunction, and hypertrophy (log-rank P <0.0001). Conclusions—: Low GLS measured by 2-dimensional speckle tracking predicts future cardiovascular events independent of conventional risk factors. Left ventricular midwall strain represents a simple echocardiographic measure, which might be used for assessing cardiovascular risk in a population-based cohort. Abstract : Supplemental Digital Content is available in the text.